2009
DOI: 10.1128/aem.02919-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gene Cluster for the Biosynthesis of a Long, Galactose-Rich Exopolysaccharide in Lactobacillus rhamnosus GG and Functional Analysis of the Priming Glycosyltransferase

Abstract: Cell surface polysaccharides have an established role as virulence factors in human bacterial pathogens. Less documented are the biosynthesis and biological functions of surface polysaccharides in beneficial bacteria. We identified a gene cluster that encodes the enzymes and regulatory and transporter proteins for the different steps in the biosynthesis of extracellular polysaccharides (EPS) of the well-documented probiotic strain Lactobacillus rhamnosus GG. Subsequent mutation of the welE gene, encoding the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
280
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 240 publications
(294 citation statements)
references
References 60 publications
(80 reference statements)
11
280
0
3
Order By: Relevance
“…This not only indicated that the MBF antiserum was functional but also provided visual evidence for the surface localization of the MBF homolog in this related L. rhamnosus strain. Since these two genetically similar L. rhamnosus strains have been reported to differ in the composition of their EPS layers (21,23), we suspected that the longer galactose-rich EPS repeating units found in L. rhamnosus GG, but not in L. rhamnosus LC705, might be the reason for the observed difference in surface-localized MBF protein.…”
Section: Rhamnosus Gg Mbf Adheres To Human Intestinal Mucusmentioning
confidence: 86%
See 3 more Smart Citations
“…This not only indicated that the MBF antiserum was functional but also provided visual evidence for the surface localization of the MBF homolog in this related L. rhamnosus strain. Since these two genetically similar L. rhamnosus strains have been reported to differ in the composition of their EPS layers (21,23), we suspected that the longer galactose-rich EPS repeating units found in L. rhamnosus GG, but not in L. rhamnosus LC705, might be the reason for the observed difference in surface-localized MBF protein.…”
Section: Rhamnosus Gg Mbf Adheres To Human Intestinal Mucusmentioning
confidence: 86%
“…As these results would imply, MBF proteins are responsible for mediating a low level of mucosal adhesion in L. rhamnosus GG and LC705 cells. Consequently, whereas MBF likely represents one of the key mucus adhesins on the cell surface of the less adhesive L. rhamnosus LC705 strain, this surface-localized (23), which was recently reported to wield a shielding effect against host protective factors (24), WT L. rhamnosus GG cells are apparently able to mediate mucosal adhesion through the surface-localized MBF. This might reflect the need for a closely interwoven association between the L. rhamnosus GG cell surface and the mucosal layer so that MBF proteins can bind optimally to mucus-related molecules.…”
Section: Vol 77 2011 Mucus-specific Surface Adhesin From L Rhamnosmentioning
confidence: 99%
See 2 more Smart Citations
“…Other cell surface components putatively involved in hostcell interactions (29,30) and potentially implicated in promoting beneficial health effects are the cell envelope-bound or -secreted EPSs. The EPS biosynthetic gene cluster (LCILS3) in the genome of strain LC705 (Fig.…”
Section: Resultsmentioning
confidence: 99%